Combustion-process derived comparable performances of Zn-(In:Sn)-O thin-film transistors with a complete miscibility - Jiang, Qingjun; Lu, Jianguo; Cheng, Jipeng; Li, Xifeng; Sun, Rujie; Feng, Lisha; Dai, Wen; Yan, Weichao; Ye, Zhizhen (Applied physics letters, 2014)
Amorphous zinc-indium-tin oxide (a-ZITO) thin-film transistors (TFTs) have been prepared using a low-temperature combustion process, with an emphasis on complete miscibility of In and Sn contents. The a-ZITO TFTs were comparatively studied in detail, especially for the working stability. The a-ZITO TFTs all exhibited acceptable and excellent behaviors from Sn-free TFTs to In-free TFTs. The obtained a-ZTO TFTs presented a field-effect mobility of 1.20 cm2 V−1 s−1, an on/off current ratio of 4.89 × 106, and a long-term stability under positive bias stress, which are comparable with those of the a-ZIO TFTs. The In-free a-ZTO TFTs are very potential for electrical applications with a low cost.